Improved analysis on the fin reliability of a plate fin heat exchanger for usage in lng applications - Saggu, M.H. (MDPI AG, 2020)
A plate fin heat exchanger (PFHE) is a critical part of the cryogenic industry. A plate fin heat exchanger has many applications, but it is commonly used in the liquefied natural gas (LNG) industry for the gasification/liquefaction process. During this gasification to the liquefaction process, there is a large temperature gradient. Due to this large temperature gradient, stresses are produced that directly influence the braze joint of PFHE. Significant work has been carried out on heat transfer and the flow enhancement of PFHE; however, little attention has been paid to structural stability and stresses produced in these brazed joints. Due to these stresses, leakages in PFHE are observed, mostly in braze joints. In the current study, standard fin design is analyzed. In addition, the structural stability of brazed joints under standard conditions is also tested. Two techniques are used here to analyze fins, using the finite element method (FEM), first by examining the whole fin brazed joint on the basis of experimentally calculated yield strength and second by dividing the braze seam into three sections and defining individual strength for each section of the seam to find stress magnitude on the basis of heat-affected zones. Moreover, by using two different techniques to analyze brazed joints, the stresses in the lower face of the brazed joint were increased by 13 and decreased by 18 in the upper face using different zone techniques as compared to standard full braze seam analysis. It can be concluded that different zone techniques are better in predicting stresses as compared to simple full braze seam analysis using the finite element method since stresses along the lower face are more critical. Â© 2020 MDPI AG. All rights reserved.